ANTECEDENTS OF PRICE ADAPTATION STRATEGY AND ITS IMPACT ON EXPORT PERFORMANCE OF SERBIAN FIRMS - Njegić, Katarina (Radosavljević); Đokić, Ines (International Journal of Economic Practice and Policy, 2019)
Previous studies on the impact of price adaptation strategy on export performance (EP) have yielded contradictory results. The aim of this paper is to examine the impact of price adaptation strategy on EP, relying on a contingency approach. The model proposed in this paper examines how the level of competition in export markets, export commitment and the availability of skilled personnel influence the adoption of price adaptation strategy and in which way price adaptation contributes to the achievement of export results. The model was tested on a sample of 60 exporters that are operating in the Republic of Serbia, and the survey was related to the business year 2017. The statistical method used was structural equation modelling through partial least squares (PLS-SEM). The results obtained indicate that there is a direct and positive impact of the level of competition on export commitment. It was found that the level of price adaptation and the availability of skilled personnel have direct and positive influence on EP. The testing of the indirect relationships between variables in the model has shown that the level of competition through the increase of export commitment affects the level of price adaptation. It was also shown that export commitment and the level of price adaptation fully mediate the relationship between the level of competition and EP. Based on the research results, conclusions for the researchers are suggested, recommendations for export business managers in Serbia, as well as the guidelines for future research.